Preservation of Fluorescence Signal and Imaging Optimization for Integrated Light and Electron Microscopy - Baatsen, Pieter; Gabarre, Sergio; Vints, Katlijn; Wouters, Rosanne; Vandael, Dorien; Goodchild, Rose; Munck, Sebastian; Gounko, Natalia V. (Frontiers in Cell and Developmental Biology, 2021)
Life science research often needs to define where molecules are located within the complex environment of a cell or tissue. Genetically encoded fluorescent proteins and or fluorescence affinity-labeling are the go-to methods. Although recent fluorescent microscopy methods can provide localization of fluorescent molecules with relatively high resolution, an ultrastructural context is missing. This is solved by imaging a region of interest with correlative light and electron microscopy (CLEM). We have adopted a protocol that preserves both genetically-encoded and antibody-derived fluorescent signals in resin-embedded cell and tissue samples and provides high-resolution electron microscopy imaging of the same thin section. This method is particularly suitable for dedicated CLEM instruments that combine fluorescence and electron microscopy optics. In addition, we optimized scanning EM imaging parameters for samples of varying thicknesses. These protocols will enable rapid acquisition of CLEM information from samples and can be adapted for three-dimensional EM.